Flood vulnerability assessment in urban areas in Kuala Lumpur, Malaysia - Nasiri, Hajar (2018)
The District Flood Vulnerability Index (DFVI) is a composite index that allows direct comparison of the relative overall flood vulnerability of urban districts worldwide, and describes the relative contributions of various factors to that overall risk. The methodology involves two concepts. First, vulnerability, which covers three related conceptions named factors of vulnerability: exposure, susceptibility and resilience. The other conception concerns the actual flooding; considerate which elements of a system are suffering from this natural disaster. Four main components of a system are recognized which are affected by flooding: social, physical, environmental and economic components. The interaction among the vulnerability factors and the components attends as the base of the recommended methodology. The development of the DFVI brings together a body of knowledge about flood risk vulnerability from a wide range of Disciplines to offer three principal benefits. First, the direct comparison of general flood vulnerability provides a useful tool for inter-city allocation of mitigation resources and effort. Most previous work in flood risk assessment has focused on a single component of the risk, and/or on a single region. The DFVI provides a systematic way to directly compare the overall flood risk vulnerability across a large number of districts or urban regions. Second, the disaggregated DFVI will increase awareness of the wide range of factors on which a district’ vulnerability depends, from the expected runoff amount, to the number of inhabitants, to a district’s existing economic condition. A comprehensive DFVI will highlight the fact that even in urban regions with low vulnerability, a flood may occur, and if it does, the other characteristics of the area could turn that single event into a major disaster. Third, by reassessing the index periodically, the DFVI may be used to monitor trends in flood vulnerability over time. The DFVI has been developed using the following six-step procedure: (1) create a conceptual framework of all the factors that contribute to flood vulnerability—social, physical, environmental and economic factors; (2) identify simple, measurable indicators to represent each of the factors in the framework (e.g., population, dominant land use of each district, precipitation, percentage of the green and open space); (3) combine the indicators Mathematically into the composite DFVI; (4) gather data and evaluate the DFVI for each of the Kuala Lumpur major districts, (5) perform a sensitivity analysis to determine the robustness of the results, (6) interpret the numerical findings to assess their reasonableness and implications, and present the results in a variety of easily understandable graphical forms. A six sample analysis was conducted to explore the challenges associated with this process, and to illustrate its feasibility. Regards to findings of this research In the Kuala Lumpur districts, Wangsa Maju is the most socially vulnerable to floods, followed by the City Centre, and Damansara is determined the least vulnerable zone. The high social vulnerability of Wangsa Maju is mainly due to its maximum population density relative to all the Kuala Lumpur zones. In considering physical vulnerability, it was revealed that the high physical vulnerability index of the City Centre zone is the consequence of high number of low cost and old buildings in this area, Damansara has the least vulnerability in terms of physical vulnerability. Comparing the results of environmental DFVI, it can be seen that Wangsa Maju has a higher environmental vulnerability and the smallest value of environmental vulnerability index belongs to Bandar Tun Razak, It is apparent from the results of economic vulnerability index comparison between Kuala Lumpur zones that Sentul has the highest economic vulnerability index where Damansara has the lowest economic vulnerability index. Combining the four main components vulnerability results in overall DFVI values shows all districts of Kuala Lumpur place in vulnerable districts category special Wangsa Maju and city center zones have high vulnerability to flood.